A quick test of cognitive speed (AQT): regression-based norms for cognitively healthy 80 to 94-year olds. Issue 5 (3rd September 2022) - Classon, Elisabet; van den Hurk, Wobbie; Wressle, Ewa; Rehn, Inger; Johansson, Maria M.
ABSTRACT: Slowed processing speed is part of normal aging but also a symptom of many diseases, including dementia. A Quick Test of Cognitive Speed (AQT) consists of three conditions: color naming (AQT1), form naming (AQT2) and dual color-form naming (AQT3) and offers a user-friendly assessment of processing speed that is used internationally to identify cognitive impairment in elderly patients. Appropriate age-norms have however been lacking. This study provides regression-based norms derived from a Swedish sample of 158 cognitively healthy 80 to 94-year olds. The results show age effects in all three conditions, a non-linear education effect in AQT1, and age by gender interactions in AQT2 and AQT3: men performed worse with increasing age, but women remained on a par. However, irrespective of age and gender, AQT2 and AQT3 mean raw and predicted scores were slower than the hitherto recommended cutoff criteria for suspected cognitive impairment.